Response of the Asian summer monsoons to idealized precession and obliquity forcing in a set of GCMs. (15th May 2018) - Bosmans, J.H.C.; Erb, M.P.; Dolan, A.M.; Drijfhout, S.S.; Tuenter, E.; Hilgen, F.J.; Edge, D.; Pope, J.O.; Lourens, L.J.
Abstract: We examine the response of the Indian and East Asian summer monsoons to separate precession and obliquity forcing, using a set of fully coupled high-resolution models for the first time: EC-Earth, GFDL CM2.1, CESM and HadCM3. We focus on the effect of insolation changes on monsoon precipitation and underlying circulation changes, and find strong model agreement despite a range of model physics, parameterization, and resolution. Our results show increased summer monsoon precipitation at times of increased summer insolation, i.e. minimum precession and maximum obliquity, accompanied by a redistribution of precipitation and convection from ocean to land. Southerly monsoon winds over East Asia are strengthened as a consequence of an intensified land-sea pressure gradient. The response of the Indian summer monsoon is less straightforward. Over south-east Asia low surface pressure is less pronounced and winds over the northern Indian Ocean are directed more westward. An Indian Ocean Dipole pattern emerges, with increased precipitation and convection over the western Indian Ocean. Increased temperatures occur during minimum precession over the Indian Ocean, but not during maximum obliquity when insolation is reduced over the tropics and southern hemisphere during northern hemisphere summer. Evaporation is reduced over the northern Indian Ocean, which together with increased precipitation over the western Indian Ocean dampens the increase of monsoonal precipitation over the continent. The southern tropical Indian Ocean as well as the western tropical Pacific (for precession) act as a moisture source for enhanced monsoonal precipitation. The models are in closest agreement for precession-induced changes, with more model spread for obliquity-induced changes, possibly related to a smaller insolation forcing. Our results indicate that a direct response of the Indian and East Asian summer monsoons to insolation forcing is possible, in line with speleothem records but in contrast to what most marine proxy climate records suggest.